Impact of Susceptibility to Global Consumer Culture on Commitment and Loyalty in Halal Cosmetic Brands - Kamila, Tasya; Negoro, Dimas Angga (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
Given that the market is becoming more competitive, it is imperative to understand what influences purchasing decisions of global consumers as consumer trends change regarding halal cosmetics for anti-aging, maintaining appearance and skin health. This study considers and examines susceptibility to global consumer culture (SGCC) (conformity to consumer trend, social prestige, and quality perception) and its effect on affective commitment, which in turn influences behavioral commitment and loyalty in the context of the halal cosmetic industry. The results are as follows. First, conformity to consumer trends has a significant effect on both emotional commitment and behavioral commitment. Second, social prestige has significant direct effect on emotional commitmen, but is not positively associated with behavioral commitment. Third, quality perception has no significant impact on emotional commitment or behavioral commitment. Finally, both emotional commitment and behavioral commitment affect brand loyalty, and behavioral commitment in particular has a significant effect on brand loyalty.